. Serum Neuroprotection , nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and superoxide dismutase (SOD) Levels in Neonates with Hypoxic-ischemic Encephalopathy: Serum Neuroprotection , nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and superoxide dismutase (SOD) Levels in Neonates - Wang, Xuan (Journal of Medical Biochemistry, 2025)
Abstract: Neonatal hypoxic-ischemic encephalopathy (HIE) is one of the main causes of brain injury and death in infants. This article aimed to investigate the effects of mild hypothermia therapy on neuroprotection and cytokine levels in neonates with HIE. 132 children with HIE in the Northwest Women’s and Children’s Hospital between January 2022 and April 2023 were enrolled as the study subjects, and they were grouped by the method of random number table, controls using conventional treatment intervention, mild hypothermia group adopting mild hypothermia therapy based on conventional treatment. The levels of cytokines and neonatal behavioral neurological assessment (NBNA) were compared before and following remedy. As against controls, in mild hypothermia therapy-treated subjects, the levels of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), and superoxide dismutase (SOD) were clearly raised; the levels of malondialdehyde (MDA), interleukin (IL-18), and Caspase-3 were clearly decreased, and the NBNA score of mild hypothermia therapy-treated subjects was clearly raised; the recovery time of neurological function was clearly shortened (all P <0.05). Mild hypothermia therapy has an obvious neuroprotective outcome on neonates with HIE, possibly by regulating the levels of cytokines.